2013
DOI: 10.1177/0960327112468178
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates methotrexate-induced hepatotoxicity in rats via inhibition of lipid peroxidation

Abstract: Hepatotoxicity is one of the major complications of methotrexate (MTX) therapy. This study was carried out to evaluate the possible protective effect of resveratrol (trans-3,5,4'-trihydroxystilbene, RVT) against MTX-induced hepatotoxicity. Rats were randomly divided into four groups as control, MTX treated (7 mg/kg/day, intraperitoneally (i.p.), once daily for 3 consecutive days), MTX + RVT treated (20 mg/kg/day, i.p.), and RVT treated. First dose of RVT was administrated 3 days before the MTX injection and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 57 publications
14
62
0
Order By: Relevance
“…There is an increasing interest in RV, since RV may prevent or delay the ischemic and chemicallyinduced injuries, multi-organ dysfunctions, inflammations, infections, and heart disorders by inhibiting oxidation and the expression of inflammatory mediators and also by regulating microcirculation (3-6,9,27). Dalaklioglu et al (28) found that RV treatment (20 mg/kg/day, ip) significantly prevented methotrexate-induced hepatotoxicity, as indicated by alanine transaminase, aspartate aminotransferase, and alkaline phosphatase levels and liver histopathology. RV significantly reduced the elevated levels of TBARS and activities of catalase and glutathione-S transferase in the hepatic tissue compared to the methotrexate-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest in RV, since RV may prevent or delay the ischemic and chemicallyinduced injuries, multi-organ dysfunctions, inflammations, infections, and heart disorders by inhibiting oxidation and the expression of inflammatory mediators and also by regulating microcirculation (3-6,9,27). Dalaklioglu et al (28) found that RV treatment (20 mg/kg/day, ip) significantly prevented methotrexate-induced hepatotoxicity, as indicated by alanine transaminase, aspartate aminotransferase, and alkaline phosphatase levels and liver histopathology. RV significantly reduced the elevated levels of TBARS and activities of catalase and glutathione-S transferase in the hepatic tissue compared to the methotrexate-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques proved that the reticuloendothelial cells were damaged by ionizing radiation, which might result in malfunction of the Kupffer cells and or a decrease in their number [28]. Histological findings of MTX-induced hepatotoxicity are including macrovesicular steatosis, hepatocellular necrosis and inflammation, edema, fibrosis, morphological abnormalities and development of cirrhosis [29][30][31]. Chemotherapeutic agents caused drug induced acute hepatitis and hepatomegaly, decreased liver enhancement and widening of periportal space due to edema which are nonspecific imaging findings of acute hepatitis [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is metabolized to curcumin glucuronides, sulfates, tetrahydrocurcumin and hexacurcumin in the intestine and liver of human and rats and is reported to exhibit antioxidant, anti-inflammatory, choleretic, anti-carcinogenic, antiviral, and anti-infectious activities. [156,157] It inhibits the expression of the enzyme cyclooxygenase 2 via interference with activation of the transcription factor NF-κB and is a potential hepatoprotectant. [158,159] Some study showed the curcumin-mediated protection against paracetamol-induced liver damage by restoring antioxidant activity of liver.…”
Section: Curcuminmentioning
confidence: 99%